TINJAUAN SOSIOLINGUISTIK BAHASA ALAY DALAM KONSTELASI KEBAHASAAN - Andri Wicaksono; Supriyono Supriyono (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
This research was conducted to get an in-depth explanation of: 1) the form of using alay language in association; and 2) the reasons behind the use of alay language in the language space. The study used a qualitative approach with observation with transcription steps, data classification based on domains, and analysis of language shift indicators and looking for factors that caused language shifts. The results of the study show that: 1) The characteristics of slang with the category of alay are its strange writings and beyond reason and common sense. Its existence can enrich linguistic studies. Such spelling style demonstrates full competence over Indonesian orthography. Users of the alay spelling style have practiced their spelling in its proper place in more casual language spaces, such as on social networking sites, private chats, and instant messages; 2) Alay language appears for the first time since the SMS (Short Message Service) program or short messages from operator services that charge per character tariff which serves to save costs. Educators should not need to be overly nervous because they think the development of "Alay Language" can damage Indonesian. Alay language which is widely used by the younger generation of Indonesia only has the condition that it threatens and damages Indonesian if it is used in inappropriate media. The current Alay language reflects an arbitrary, random, and arbitrary culture; up to.